PENGELOLAAN KEUANGAN PESANTREN - Aep Tata Suryana (STAI Sebelas April Sumedang, 2020)
The purpose of this research is to find out the description of pesantren financial management. By the title of the research, the research uses the literature method. The results of the study explained that financial management is an act of financial administration/administration which includes recording, planning, implementation, accountability, and reporting. Thus, school financial management can be interpreted as a series of activities regulating school finance from planning, accounting, spending, supervision, and accountability of school finances. Financial management of boarding schools is one of the substances of the management of educational institutions that will also determine the smooth operation of boarding schools. As is the case with the substance of education management in general, financial management activities in Islamic boarding schools should be carried out through the processes of planning, organizing, directing, coordinating, supervising, or controlling. Some financial management activities take the form of obtaining and determining sources of funding, use of funds, reporting, auditing, and accountability. Through financial management activities, the funding needs of Islamic boarding school activities can be planned, procured, transparently recorded, and used to finance the implementation of Islamic boarding school programs effectively and efficiently. For that purpose, the financial management of Islamic boarding schools includes: (1) Improving the effectiveness and efficiency of the use of financial boarding schools; (2) Increasing financial accountability and transparency in Islamic boarding schools; and (3) Minimizing misuse of the boarding school budget.